2018
DOI: 10.1186/s12906-018-2359-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of the anti-allergic and anti-inflammatory activity of Brachychiton rupestris and Brachychiton discolor leaves (Malvaceae) using in vitro models

Abstract: BackgroundBrachychiton rupestris and Brachychiton discolor (Malvaceae) are ornamental trees native to Australia. Some members of Brachychiton and its highly related genus, Sterculia, are employed in traditional medicine for itching, dermatitis and other skin diseases. However, scientific studies on these two genera are scarce. Aiming to reveal the scientific basis of the folk medicinal use of these plants, the cytotoxicity, anti-inflammatory and anti-allergic activities of Brachychiton rupestris and Brachychit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Recent anti-inflammatory studies on phytosterols showed that stigmasterol did not produce a significant anti-inflammatory effect in vitro but performed better in a topical application. 50–52 The prenylated steroid glycoside ( 15 ) has not been tested for anti-inflammation but closely related compounds have been claimed to possess good anti-inflammatory properties. 53 , 54 Structural similarity of these steroidal molecules to those of known single agent anti-inflammatory drugs suggests that they may be contributing additively to the notable anti-inflammatory activity of A. boonei's n -hexane fraction in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent anti-inflammatory studies on phytosterols showed that stigmasterol did not produce a significant anti-inflammatory effect in vitro but performed better in a topical application. 50–52 The prenylated steroid glycoside ( 15 ) has not been tested for anti-inflammation but closely related compounds have been claimed to possess good anti-inflammatory properties. 53 , 54 Structural similarity of these steroidal molecules to those of known single agent anti-inflammatory drugs suggests that they may be contributing additively to the notable anti-inflammatory activity of A. boonei's n -hexane fraction in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Steroidal terpenoids were identified in the tested fraction. [50][51][52] Recent anti-inflammatory studies on phytosterols showed that stigmasterol did not produce a significant anti-inflammatory effect in vitro but performed better in a topical application. 53,54 The prenylated steroid glycoside (15) has not been tested for antiinflammation but closely related compounds have been claimed to possess good anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 100 g of air-dried P. odorata Blanco (Lamiaceae) leaves were ground into a fine powder and exposed to exhaustive maceration in neat methanol (3 × 1 L) and subsequently filtrated at 45 °C in vacuo using Rotavap (Buchi Rotavapor R-114 coupled with Buchi Vac V-500 pump, Switzerland) until completely dried and then lyophilized to give 9.8 g of total methanol extract. An amount of 9 g of the lyophilized powder was solubilized in 70% methanol and subsequently fractionated using 3 L of distilled n -hexane to give 0.5 g of n -hexane fraction [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity was evaluated by applying the MTT cell viability assay ( Van de Loosdrecht et al, 1991 ; Thabet et al, 2018b ). Briefly, this assay depends on the conversion of MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) by the viable cells from the yellow color to purple formazan compound.…”
Section: Biological Assessmentsmentioning
confidence: 99%